THE REPRESENTATION OF ISLAMIC CHARACTERS IN ENGLISH TEXTBOOKS USED BY SENIOR HIGH SCHOOLS IN BENGKULU - Hasiyanti Hasiyanti; Safnil Arsyad (Universitas Pamulang, 2023)
Religious values are needed in textbooks and learning process, such as in English Language Teaching (henceforth ELT) for both the student and teachers to support character education as suggested by the government of Indonesia. Indonesian people have more than one believes or religion and the most dominant one is Islam. This is important because Islamic characters can be an alternative media for students and teachers in the teaching and learning processes. There were three grades of English textbooks chosen in this investigation. The results showed that there are three aspects of religious values: ritual, social and material and the majority found in the textbooks was material aspect. In addition, there are two ways how Islamic characters are represented in the textbooks: visual and non-visual. The second result showed that the dominant value aspect is visual. This implies that English textbooks used by senior high school do not focus on ritual, social and non-visual aspects in developing English textbooks.